Historical biogeography of five characidium fish species: dispersal from the amazon paleobasin to Southeastern South America - Poveda-Martínez, Daniel; Sosa, Chrystian C.; Chacón-Vargas, Katherine; García Merchán, Víctor Hugo (Public Library of Science, 2016)
Characidium is a Neotropical fish genus. Its distribution ranges from eastern Panama to northern Argentina, and it is an important component of the Neotropical ichthyofauna present in the major rivers of South America. We here provide an approximation to the dispersal and historical distributions of Characidium. The biogeographic history of five species of the genus was analyzed through nuclear RAG-2 and mitochondrial 16S genes and a time-calibrated phylogenetic analysis using three outgroup species. A biogeographical reconstruction was performed to estimate ancestral geographic ranges and infer the historical events that impacted the geographic distributions of Characidium species. Our results showed Characidium as a monophyletic group. The molecular clock suggests that the most recent common ancestor of Characidium originated during the Eocene, about 50.2 Mya. In addition, different dispersion and vicariance events could be inferred, which possibly gave rise to the present geographical distribution of the genus. Our results point to the rise of the Andean mountains and sea fluctuations as being important events in the formations and delimitation of different rivers, which influenced the distribution of South American ichthyofauna.